Analisis Perlindungan Hukum Terhadap Pemberi Kerja di Indonesia dalam Hukum Ketenagakerjaan Tahun 2024 - Mukhasibi, Muhammad Akmal (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to analyze legal protection for employers/businessmen/companies harmed by irresponsible workers in the Indonesian employment landscape in 2024. This study uses a normative legal method with a descriptive approach. The results of the study indicate that the Job Creation Law brings changes to the regulation of fixed-term employment agreements in the Employment Law, but there are still several issues that need attention. Legal protection for workers and employers is regulated in the Employment Law. Enforcement of employment law is carried out through strict supervision to maintain a balance between the rights and obligations of employers and workers. This research is expected to contribute to the development of employment law science, especially regarding legal protection for employers.